Prevalence of Fascioliasis among cattle and goats slaughtered in Shah Alam abattoir - Ismail, Fatin Fazira (2018)
Fascioliasis in livestock is veterinary and public health importance causing serious economic losses. However, there are very few data on abattoir level. The present study investigated the prevalence of fascioliasis in cattle and goat slaughtered in the Shah Alam abattoir. A convenience sampling used to determine the prevalence of Fasciola sp. in the abattoir. Liver was examined for any abnormalities and bile ducts were incised for present of fluke. Of 80 liver samples examined, 1.25% (1 out of 80 samples) were positive for infection of Fasciolagigantica in cattle and a total of 25 liver flukes was present. None of goat liver samples positive for Fasciola sp.